Recent Progress in Chemical Vapor Deposition of 2D Magnetic Materials - Yuan, Shuyang; Zhou, Yanchang; Yin, Lei; Wang, Xintian; Jiang, Sheng; Song, Ziyi; Wen, Yao; Cheng, Ruiqing; He, Jun (Advanced Physics Research, 2025)
Magnetic 2D materials have gotten significant attention due to their unique low‐dimensional magnetism and potential applications in advanced spintronics, providing an perfect platform for investigating magnetic properties at the 2D limit. The chemical vapor deposition (CVD), known for its simplicity and strong controllability, has become a key technique for fabricating ultrathin magnetic nanosheets. This article systematically reviews recent advancements in CVD‐grown magnetic 2D materials, focusing on the effects of growth parameters on material morphologies and properties, and analyzing the construction of heterostructures and their role in magnetic regulation. In addition, various magnetic characterization methods are introduced, and potential applications of these materials in spintronic devices are discussed. By summarizing current challenges, the article provides insights into future research directions, emphasizing the need to improve material stability, Curie temperature, and scalable synthesis to enable practical applications of 2D magnetic materials. Magnetic 2D materials have gotten significant attention due to their unique low‐dimensional magnetism and potential applications in spintronics. This review summarizes and analyzes the key factors and control strategies in the CVD growth of 2D magnetic materials. Additionally, it provides an overview of commonly used magnetic characterization techniques and applications of 2D magnetic materials in spintronic devices.